La pêcherie migrante des petits pélagiques côtiers et l’approvisionnement de l’industrie de la farine et de l’huile de poisson en Mauritanie - Assane Dedah Fall; Elimane Abou Kane; El hadj Bara Dème; Pierre Failler; Abdou Daim Dia (Belgeo)
The aim of this article is to analyse the contribution of the Senegalese and Turkish migrant fisheries for small coastal pelagics to the supply of the fishmeal and fish oil industries in Mauritania. The data used are those relating to Senegalese pirogues and Turkish coastal boats. Both types of vessel operate in the area reserved exclusively for coastal fishing. This work is based mainly on IMROP data. Other data were also used : those from the Ministry of Fisheries and those collected during field surveys carried out between 2019 and 2022 along the coastline. The results show that the migratory pelagic fishery has a significant impact on the development of the processing industry and the exploitation of fishery products in Mauritania. Migrant catches will amount to around 540,000 tonnes by 2020, and will also help to meet Mauritanians’ food requirements for fish by supplying local and inter-city fish markets through the SNDP. However, the migratory fishery for small coastal pelagics has a limited impact on Mauritania’s socio-economic development. The foreign currency earnings generated by the fishmeal and fish oil industry remain abroad and do not benefit the country. The industry’s impact on promoting employment remains very weak, even marginal, with a large foreign workforce. The situation of pelagic fisheries in Mauritania has also raised serious sustainability issues in recent years. Rigorous co-management measures should be taken at national and regional level to ensure the sustainable management of stocks, which are already showing signs of depletion.